Holocaust education in transition from live to virtual survivor testimony: pedagogical and ethical dilemmas. Issue 3 (3rd July 2022) - Marcus, Alan S.; Maor, Rotem; McGregor, Ian M.; Mills, Gary; Schweber, Simone; Stoddard, Jeremy; Hicks, David
ABSTRACT: This article explores the pedagogical challenges and ethical dilemmas related to the use of Virtual Interactive Holocaust Survivor Testimony (VIHST) in place of live survivor testimony. The National Holocaust Centre and Museum (UK) uses 3D interactive digital as an attempt to replicate the meaningful learning experiences of listening to a live survivor. Data was collected through interviews with survivors and museum staff. Key findings include how survivors are chosen to participate, whether testimonies can or should be edited for pedagogical purposes, and challenges associated with virtual testimony that do not exist with live survivor testimony.